A Systematic Literature Review on Urban Logistic in A Sharing Economy - ROSELAN, MUHAMAD HILMAN; HANIF , AZLINA; RASHID, ARLINAH ABD (Journal of Ecohumanism, 2024)
The sharing economy is fundamentally transforming urban logistics, presenting both opportunities and challenges. This systematic literature review investigates the key research themes and methodologies employed in studying this dynamic field. We conducted a comprehensive search in corpus analysing numbers of peer-reviewed articles to address what is the main topics and challenges explored in urban logistics within the sharing economy and how this research methodologies related to this main topic. The paper discusses the main evidence emerging from a systematic literature review (SLR) on urban logistics. The corpus resulting from the SLR has been used to perform a citation network analysis and a main path analysis that together underpin the identification of the most investigated topics and methodologies in the field. Through the analysis of a corpus of 109 articles, our findings reveal that urban logistics in the sharing economy faces several prominent challenges, including traffic congestion, pollution, and last-mile delivery. Studies consistently emphasize the crucial role of technology in addressing these issues, highlighting innovations such as route optimization, real-time tracking, and alternative delivery methods. Furthermore, we identified the growing importance of policy interventions in promoting sustainable and efficient practices. Studies explored the implementation of measures like congestion pricing and urban logistics zones, reporting positive outcomes such as improved traffic flow, reduced emissions, and optimized use of urban logistics spaces. This systematic review contributes significantly to the field of urban logistics in the sharing economy in identifying key thematic areas and highlighting their specific relevance to the sharing economy context. By doing so, it will offer valuable insights and recommendations for future research, emphasizing the need for further exploration of the long-term impacts of technological innovations and policy interventions, as well as the integration of diverse methodological approaches for a comprehensive understanding of this complex and evolving field.